Development of technology of using substandard eggs in farm poultry feeding - Iegorov, Bohdan; Vorona, Nina; Маkarynska Аllа; Voietska, Olena; Bordun, Tatiana (Eastern-European Journal of Enterprise Technologies, 2016)
Theoretically and experimentally, there was substantiated the expediency of enriching grain raw material in the composition of feed with the protein of animal origin due to a substantial reduction of nutritional and energy value of the grain components that are produced in Ukraine, often with violation of agrotechnology. The possibility to use valuable substandard egg mass for feeding agricultural poultry was proved. This will allow solving the problem of utilizing defective eggs. A technological way of producing the extruded feed additive was developed, which implies obtaining the preceding mixture of crushed corn and egg mass without shell of substandard chicken eggs in the 1:1 ratio in a frame mixer for 180 s, mixing the preceding mixture with corn grit, which remained in the blade batcher for 120…180 s, and the extrusion of the resulting highly homogeneous mixture. The rational parameters of technological process of the extrusion of the feed additive were established: pressure in the working zone of the extruder is 2...3 MPa, power consumption of the electromotor is 4.0...4.5 kW, product temperature at the outlet of the extruder is 110…120 ºC, duration of the process is 60...120 s, diameter of the hole of the matrix is 10 mm. The optimum amount of the egg mass in the mixture is 10 %. The influence of the extrusion process on the quality and nutritional value of the extruded feed additive was defined. During the extrusion process, the 3,1 % loss of crude protein content was observed, the starch content decreased by 26.8 %, in this case, the content of watersoluble carbohydrates increased by 6 times. During the storage of the extruded feed additive for 3 months, bacterial semination decreased by 7 times. Biological assessment of efficiency of the improved technology of the production of extruded feed additive was defined on laboratory animals, and it was found that the extruded feed additive is characterized by high biological value, so in the tested group the daily average gain of live weight of rats was 25,4 % higher, and the conversion of feed was 20.3 % lower than in the control group.